Employee Development : Coaching and Mentoring Approach to Sustainability Organization - Rinto Andrianto; Supardi Supardi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article will explore the importance of employee development and coaching and mentoring approaches in achieving organizational sustainability. We will explore the benefits of combining these two approaches, examples of successful implementation, and best practices that can be applied by organizations seeking to achieve sustainability in their operations.In this study, analysts used to review observational data from several major research sources, focusing on human resources. It is thought that the results of publications from various organizations and industrial fields are important to researchers, and it is believed that by analyzing such works, analysts can provide speculative ideas that drive research. Scientific articles that make reinforcement for scientific articles in participation contribute to science and especially the scientific articles above can represent with existing limitations with findings that provide a result for this scientific article in literature.